Physical simulation of temperature influence on methane sorption and kinetics in coal: Benefits of temperature under 273.15 K. (15th October 2015) - Wang, Zhaofeng; Tang, Xu; Yue, Gaowei; Kang, Bo; Xie, Ce; Li, Xiaojun
Highlights: Freezing core sampling technique (FCST) is proposed for coal coring sampling. Isothermal adsorption and diffusion tests under 273.15 K were conducted. The adsorption capacity of anthracite increases linearly with decreasing temperature. The mean isosteric heat of adsorption can evaluate the adsorptivity of coal. The unipore diffusion model is used to describe the methane diffusion in coal. Abstract: To decrease the lost gas content in the core sampling process and make the lost gas content estimation more accurate in CBM (coalbed methane) gas-in-place estimation, the freezing core sampling technique (FCST) is proposed for coal core sampling and physical simulation of the technique is conducted. The low temperature influence on methane adsorption capacity and kinetic properties in crushed coal are investigated. Isothermal adsorption tests under low temperatures (from 243.15 K to 303.15 K) were conducted. Test results support that the low temperature (under 273.15 K) greatly inhibits methane transport in coal while enhancing methane adsorption capacity in coal. Due to its unique temperature independence the mean isosteric heat of adsorption is used to evaluate adsorptivity of coal, and the mean isosteric heat of adsorption of the tested anthracite is 23.31 kJ/mol. The low temperature (under 273.15 K) decreases kinetic parameters, such as diffusion content and the diffusion coefficient, in the isothermal diffusion process. The diffusion content is controlled by both temperature and pressure, and high pressure weakens the temperature effect on diffusion content in coal. Diffusion coefficients decrease from 5.13 × 10 −12 cm 2 /s to 3.34 × 10 −12 cm 2 /s when temperature decreases from 303.15 K to 233.15 K. Therefore, this study suggests that using the freezing core sampling technique can be implemented in future underground coal core sampling.